Case Report: Personalized Therapeutical Approaches with Lenalidomide in Del(5q): A Case Series - Stein, Anna; Kubasch, Anne Sophie; Haferlach, Claudia; Platzbecker, Uwe (Frontiers in Oncology, 2022)
Myelodysplastic Syndrome (MDS) with del(5q) represents a unique WHO entity, which is often treated with lenalidomide according to standard clinical practice (1). Guidelines concerning treatment duration have thus far not been implemented but rather comprise an indefinite therapy until loss of response. This review presents three red blood cell (RBC) transfusion dependent MDS with del(5q) cases, starting with one rare case with an unbalanced translocation t(2;5), involving the breakpoint of del(5q) and loss of the 5q15-5q31 region. To the best of our knowledge no comparable case has been described before with a response to lenalidomide. Strikingly, treatment induced and maintained cytogenetic complete remission (cCR) in this patient. Furthermore, we report two cases of classical del(5q), in which lenalidomide was interrupted at the time cCR after a short period of lenalidomide therapy. Despite drug holiday cCR was maintained for seven and nine years, respectively. Then del(5q) re-emerged in the absence of novel molecular aberrations and re-treatment with lenalidomide could again achieve cCR in both cases. Together, this series presents three cases of personalized therapy of MDS with del(5q).